O que significa Estudos de Cultura? Um diagnóstico cosmopolita sobre o caso da cultura alemã - Gil, Isabel Capeloa (2008)
The article discusses Culture Studies as a field of study negotiating its methods and paradigms vis-a-vis the social oriented Cultural Studies, as well as the hermeneutic tradition of the Kulturwissenschaften. Focusing on the case-study of German Culture, it is further argued that Culture Studies is a metadiscipline, and a problem-oriented field of study, that responds to the need to reflect complexity in the contemporary world and clearly presents the relevance of the Humanities for the disclosure of meaning in democratic societies.